2021
DOI: 10.1002/mbo3.1248
|View full text |Cite
|
Sign up to set email alerts
|

Detection of antimicrobial resistance genes in urban air

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Analyzing the land use and weather conditions during the sampling period could potentially provide valuable insights and help identify explanatory variables. Indeed, previous studies have demonstrated that the urban environment, characterized by human activities, serves as a reservoir for AMR due to factors like water disposal systems and pollution [9,61,62]. Additionally, specific molecules, including cephalosporins (CTX, FOX, KF), tetracyclines (DO, TE), and penicillins (AX), were found to be statistically associated with provincial disparities.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the land use and weather conditions during the sampling period could potentially provide valuable insights and help identify explanatory variables. Indeed, previous studies have demonstrated that the urban environment, characterized by human activities, serves as a reservoir for AMR due to factors like water disposal systems and pollution [9,61,62]. Additionally, specific molecules, including cephalosporins (CTX, FOX, KF), tetracyclines (DO, TE), and penicillins (AX), were found to be statistically associated with provincial disparities.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence has continuously shown that antimicrobial resistance has displayed its existence in various environments, such as human or animal hospitals [ 3 5 ], indigenous residents, wild animals [ 6 ], and water circumstances (including rivers, lakes, oceans, etc.) [ 7 , 8 ], soil [ 9 ], polar lands [ 10 ], food, sewage, sludge [ 11 , 12 ], and air [ 13 ]. While antimicrobial resistance genes (ARGs) have shared their specific ways to transfer via the horizontal genetic elements (HGEs), such as plasmids, integrons, transposons, and bacteriophages, among or between different species [ 14 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally in the extant literature, most airborne microorganism's characterization depended on culture-based methods [13][14][15], leading to an underestimation of the total bacterial diversity. The cultural method only recognizes 1.5-15.3% of all the species that are able to form a colony and the microorganisms that are not viable or unable to grow are not identified [16].…”
Section: Introductionmentioning
confidence: 99%
“…A dysbiosis state causes the reduction of immune-related commensal species and the increase of pathogens and pathobionts (commensal microorganisms which can become pathogens when genetic and environmental conditions change) [29,30]. Microorganisms that composed bioaerosol are also a reservoir for the resistome, the complex of the antimicrobial resistance genes (ARGs), further decreasing antibiotic's efficacy [15]. Exposure to PM-associated bioaerosol has been markedly associated with various health effects, mainly with infectious diseases but also respiratory diseases, allergies, and lung cancer [13,14,20,26,27,29].…”
Section: Introductionmentioning
confidence: 99%